2017
DOI: 10.1007/s00701-017-3119-y
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial pressure monitoring after primary decompressive craniectomy: is it useful?

Abstract: Intracranial hypertension is an important secondary insult after traumatic brain injury, and its control is considered to be of benefit to our patients. Intracranial pressure (ICP) monitoring is considered standard practice, at least in the developed world, in the modern neurosurgical management of traumatic brain injury. ICP waveform analysis and understanding has improved tremendously over the last few decades. However, there is still a lack of Bclass I^evidence in support of superiority of treatment based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Demetriades studied ICP in patients after DC to understand the effectiveness of DC for ICP reduction. 8 Nevertheless, literature is lacking for decisions on DC based on intraoperative ICP values.…”
Section: Discussionmentioning
confidence: 99%
“…Demetriades studied ICP in patients after DC to understand the effectiveness of DC for ICP reduction. 8 Nevertheless, literature is lacking for decisions on DC based on intraoperative ICP values.…”
Section: Discussionmentioning
confidence: 99%
“…However, elevated skin turgor does result in a later increase in ICP, within 24 hours. ICP monitoring in patients with decompressive hemicraniectomy has been controversial [14]. Several studies have shown that ICP monitors may not reflect rising ICP soon enough, as the craniectomy defect allows for herniation outside of the skull prior to damage to the brain [7,9,11].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still unclear whether ICP monitoring is practical after primary DCs. [23] In their study, Huang et al [24] elucidated the relationship between the ICP monitoring and outcomes in patients undergoing primary DC for traumatic brain injury. They reported that neurological outcomes did not differ between the patient groups with ICP monitoring and without ICP monitoring.…”
Section: Discussionmentioning
confidence: 99%